Rostrotentorial decompressive craniotomy in a breeding ram - Sandoval Monzón, Rocío Silvia (2017)
This study aimed to discuss the results of a rostrotentorial decompressive craniotomy performed in a ram with had severe neurological signs. The patient had a clinical picture of right paresis product of a left hemisphere syndrome. A computerized axial tomography (CAT) was conducted and a tumour was found in the left cerebral hemisphere. In order to extend the productive life of the animal, given his value as a sire, a decompressive craniotomy was performed. Part of the cranial vault was dissected to provide more space to the brain and relieve intracranial hypertension caused by this pathology. Once recovered from anaesthesia, the animal presented a remission of neurological signs. The patient did not present the previous compulsive circling behaviour, ataxia and head-pressing behaviour. The patient remained under observation for a period of 20 days, during which he presented good temper and appetite. The results of the surgery showed the possibility of using this technique for the relief of neurologic clinical signs in animals suffering cerebral neoplasia, cerebral oedema, cerebral bruises or coenuruses.